2016
DOI: 10.1016/j.ijrobp.2015.12.243
|View full text |Cite
|
Sign up to set email alerts
|

Reirradiation of Recurrent and Second Primary Head and Neck Cancer With Proton Therapy

Abstract: COPurpose/Objective(s): Head and neck squamous cell carcinomas (HNSCCs) afflict over half a million patients annually worldwide. In the absence of disease at distant sites, salvage treatment may provide durable disease control in only approximately 15% of such patients. Our research goal is to improve radiation therapy for aggressive HNSCCs by identifying novel targets for radiosensitization. The EphB4 receptor is ubiquitously expressed in HNSCCs and has been shown to promote tumorigenic and invasive propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 0 publications
1
25
0
1
Order By: Relevance
“…Overall, the more recent larger series seem to report locoregional control outcomes that are comparable with IMRT reports, with 2-year locoregional control rates of 73% and 80% in 2 studies compared to 50% and 60%, 14,40 respectively, among the IMRT studies. The late G3 or higher toxicity rates were 20% and 25% in the 2 studies reporting it.…”
Section: Proton Reirradiationsupporting
confidence: 52%
See 3 more Smart Citations
“…Overall, the more recent larger series seem to report locoregional control outcomes that are comparable with IMRT reports, with 2-year locoregional control rates of 73% and 80% in 2 studies compared to 50% and 60%, 14,40 respectively, among the IMRT studies. The late G3 or higher toxicity rates were 20% and 25% in the 2 studies reporting it.…”
Section: Proton Reirradiationsupporting
confidence: 52%
“…McDonald et al 40 reported on 61 patients receiving proton reirradiation primarily for skull base lesions. Proton therapy was delivered with the PSPT technique to a median dose of 66 Gy (RBE) for those with microscopic residual disease and 70.2 Gy (RBE) for those with gross disease.…”
Section: Proton Reirradiationmentioning
confidence: 99%
See 2 more Smart Citations
“…Proton beam therapy for reRT has been investigated at other disease sites including head and neck, 38,39 central nervous system, 40,41 lung, 42,43 gynecological, 44 and gastrointestinal malignancies. [45][46][47] A recent systematic review found that reRT with PBT is safe and effective.…”
Section: Discussionmentioning
confidence: 99%